Fleshy Red Algae Mats Influence Their Environment in the Mediterranean Sea - Schmidt, Neele; El-Khaled, Yusuf C.; Roßbach, Felix I.; Wild, Christian (Frontiers in Marine Science, 2021)
In the Mediterranean Sea, the fleshy red alga Phyllophora crispa forms dense mats of up to 15 cm thickness, mainly located on rocky substrates in water depths below 20 m. Because of the observed density of these mats and some first observations, we hypothesize that P. crispa is a yet undescribed ecosystem engineer that provides a multitude of ecological niches for associated organisms along small-scale environmental gradients. Therefore, we conducted an in-situ pilot study in the Western Mediterranean Sea to assess potential influence of the algae mats on the key environmental factors water movement, temperature and light intensity. We comparatively and simultaneously measured in P. crispa mats, in neighbouring Posidonia oceanica seagrass meadows, on neighbouring bare rocky substrates without algae mats, and in the directly overlying water column. We used several underwater logging sensors and gypsum clod cards. Findings revealed that P. crispa significantly reduced water movement by 41 % compared to the overlying water column, whereas water movement was not affected by P. oceanica meadows and bare rocky substrates. Surprisingly, P. crispa increased the water temperature by 0.3 °C relative to the water column, while the water temperature in P. oceanica and on bare rocky substrates was reduced by 0.5 °C. Light intensity inside the red algae mats was reduced significantly by 69 % compared to the water column. This was similar to measured light reduction of 77 % by P. oceanica. These findings highlight the strong influence of the dense red algae mats on some key environmental factors. Their influence is obviously similar or even higher than for the well-known seagrass ecosystem engineers. This may be a factor that facilitates associated biodiversity similarly as described for P. oceanica.